A study about inguinal hernia mesh repairs:plug and patch versus lichtenstein mesh repair technique - Singh, Rana Ranjit; Gupta, Arun Kumar; Shah, Avreen Singh; Singh, Rupinderjit; Singh, Angadjot (International Surgery Journal, 2016)
Background: The study was conducted on 200 patients admitted with inguinal hernias, at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, India. Methods: This study was conducted on the simple technique of mesh repair in inguinal hernia patients of type 1,2, and 3, according to Gilbert’s classification of groin hernias, in the form of randomized controlled trial of plug and patch versus Lichtenstein mesh repair technique in a group of randomly selected 100 cases of inguinal hernias each in relation to concurrent study of operating time, any intraoperative or postoperative complications, post-operative pain, length of hospital stay, recurrence rate and time taken to return to normal routine activities and work, under the regular follow up intervals of 1 week, 3 weeks and 6 month. Results: Most common in 4th decade especially in patients doing strenuous activity. Right indirect hernia was most common and between both the groups it was seen that post-operative stay was similar. Conclusions: Both the techniques, lichtenstein and plug and patch inguinal hernia repair, are equally good in terms of negligible intra-operative, post-operative complications and overall outcome with good patient compliance and satisfaction.